2022
DOI: 10.3390/v14030501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Adjuvants on Immune Responses Elicited by Protein-Based Subunit Vaccines against SARS-CoV-2 and Its Delta Variant

Abstract: The global pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become more serious because of the continuous emergence of variants of concern (VOC), thus calling for the development of broad-spectrum vaccines with greater efficacy. Adjuvants play important roles in enhancing the immunogenicity of protein-based subunit vaccines. In this study, we compared the effect of three adjuvants, including aluminum, nanoparticle manganese and MF59, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
(27 reference statements)
2
20
0
Order By: Relevance
“…No significant changes in serum Cu levels were recorded before and after vaccination. As Cu and Zn are antagonists during the absorption process in the gastrointestinal tract (GIT), higher Cu levels in the GIT could be expected to reduce Zn levels [9] . However, the opposite is also true, as zinc intake in high doses (> 150 mg/day) can result in Cu deficiency in healthy individuals [30] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant changes in serum Cu levels were recorded before and after vaccination. As Cu and Zn are antagonists during the absorption process in the gastrointestinal tract (GIT), higher Cu levels in the GIT could be expected to reduce Zn levels [9] . However, the opposite is also true, as zinc intake in high doses (> 150 mg/day) can result in Cu deficiency in healthy individuals [30] .…”
Section: Resultsmentioning
confidence: 99%
“…Following a SARS-CoV-2 infection, most patients develop detectable specific IgG antibodies to the receptor-binding domain (RBD) of the viral spike glycoprotein and associated neutralizing activities [1] , [3] , [5] , [8] , [9] . In addition, most infected persons develop detectable IgG levels to structural SARS-CoV-2 antigens that can persist for more than six months post-acute infection [10] , [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The RBD vaccination strategy demonstrated a significant impact on eliciting elevated cross-neutralizing antibody titers, with subsequent protection against viral variants and the potential to limit community transmission [45]. Zhang et al (2022) investigated the effect of adjuvants on the immunogenicity of three COVID-19 vaccine candidates, based on proteins, including RBD-Fc, RBD, and S-trimer [46]. The feasibility of inducing protective immunity against Omicron and future emerging sarbecoviruses relying on RBD was recently reported by Lui et al (2022) [47].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with RBD and S‐trimer, we found that RBD‐Fc homodimer effectively elicited more potent RBD‐specific IgG and neutralizing antibodies against SARS‐CoV‐2 and its Delta variant in mice. 61 Moreover, a COVID‐19 RBD‐dimer‐based protein subunit vaccine candidate, ZF2001, 62 exhibited high protective efficacy (more than 80%) in preventing symptomatic COVID‐19 in phase 3 clinical trials. 63 Recent studies have demonstrated that it could induce increased titers of nAbs against Omicron after administration of multiple booster doses.…”
Section: Major Antigen Targets Of Current Sars‐cov‐2 Vaccinesmentioning
confidence: 99%